Tuning the GENIE pion production model with MINERvA data - Stowell, P (2019)
CONCYTEC, Direccion de Gestion de la Investigacion-Pontificia Universidad Catolica del Peru (DGI-PUCP), and Vicerrectorado de Investigacion-Universidad Nacional de Ingenieria (VRI-UNI) (Peru); and by the Latin American Center for Physics (CLAF); NCN Opus Grant No. 2016/21/B/ST2/01092 (Poland). We thank the MINOS Collaboration for use of its near detector data. Finally, we thank the staff of Fermilab for support of the beam line, the detector, and the computing infrastructure.